Pengaruh Pemberian NaCl Terhadap Produksi Caisim (Brassica Juncea L) di Tulang Bawang Barat - Novrimansyah, Eko Abadi; Ilmiasari, Yeyen; Ayuningtyas Harini, Nyang Vania; Sunaryo, Wisnu Arief (Universitas Muhammadiyah Kotabumi, 2025)
The production of caisim plants in Tulang Bawang Barat District is still not optimal. One of the contributing factors is the inadequate use of fertilizers. The right fertilizer can enhance both the quality and quantity of plant production. One type of fertilizer frequently used by farmers is NaCl. To ensure optimal production and quality of the plants, appropriate application of NaCl is needed to avoid detrimental effects. This research aims to (1) investigate the effect of NaCl application on caisim production and (2) determine the optimal NaCl dosage that can enhance caisim production. The study was conducted in a home garden located in Makarti RT 005/RW 003, Tumijajar District, Tulang Bawang Barat, covering a total area of 10 x 50 m, with 8 x 10 m allocated for the research. The study used a randomized block design (RBD), with a total of 24 plant samples subjected to NaCl treatments: P0 (control), P1 (5 grams/liter of water), P2 (10 grams/liter of water), and P3 (15 grams/liter of water). The parameters measured in this study included the number of leaves, plant height, fresh weight, and dry weight. The data analysis techniques used were One-Way ANOVA and the Least Significant Difference (LSD) test. The results indicated that the application of NaCl fertilizer significantly affected the production of caisim (Brassica juncea L) as indicated by plant height, number of leaves, fresh weight, and dry weight in treatments with NaCl at 5 grams/liter of water (P1), 10 grams/liter of water (P2), and 15 grams/liter of water (P3), compared to the control without NaCl. The application of NaCl with a dosage of 15 grams/liter of water (P3) showed optimal results in enhancing caisim production (Brassica juncea L) in terms of plant height, number of leaves, fresh weight, and dry weight